The Effect of Brain-Based Learning (BBL) Model with Audiovisual Media on Student's High-Level Thinking Ability - Gita Dwi Wardani; Retno Dwi Suyanti; Daulat Saragi (Nazhruna: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to obtain scientific information about students' higher-order thinking skills with the Brain-Based Learning (BBL) learning model using audiovisual media guided by students' learning motivation to develop teaching materials, especially in science subjects "substances and mixtures", as well as to measure the validity, practicality, and effectiveness of science learning. The design used in this study is quasi-experimental. by using a pretest and posttest control group design. However, before the pretest, the questions tested had been tested for homogeneity considering children’s different abilities. This design involves two classes, namely the experimental group class and the control group class. From the results of the study, there are differences in students' higher-order thinking skills between classes using the Brain-Based Learning (BBL) model and types using conventional methods with an average post-test score of higher-order thinking skills using the Brain-Based Learning (BBL) model of 87,044 and the average posttest value of higher order thinking skills with conventional methods is 77,193.